2020
DOI: 10.1016/j.jdermsci.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin inhibits melanoma by regulating CTL/Treg anti-tumor immunity and STAT3-mediated apoptosis via IL-10 dependent manner

Abstract: Background: It has been shown that dihydroartemisinin (DHA) is effective in the treatment of malaria. Recently studies have demonstrated that DHA also regulates tumor cell growth, angiogenesis, T cell differentiation and generation. However, how DHA affects melanoma development remains poorly defined. Objectives: To investigate the effects of DHA on the proliferation and migration of melanoma in vivo and in vitro, and to explore its possible mechanism. Methods: B16F10 cells and melanoma-bearing BALB/c mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…The data presented above, in addition to many studies in the literature, indicate that DHA is involved in regulating the TME of cancer [ 16 , 26 ]. However, there is no publicly available information about the role of DHA in the TME of COAD.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The data presented above, in addition to many studies in the literature, indicate that DHA is involved in regulating the TME of cancer [ 16 , 26 ]. However, there is no publicly available information about the role of DHA in the TME of COAD.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies showed that DHA could inhibit COAD cell viability through regulating cell proliferation and apoptosis [15,42]. e data presented above, in addition to many studies in the literature, indicate that DHA is involved in regulating the TME of cancer [16,26]. However, there is no publicly available information about the role of DHA in the TME of COAD.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In recent years, the anticancer effects of DHA have also been confirmed in a variety of tumor models. With regard to skin cancer, the inhibitory effects of DHA on the growth of cSCC and melanoma cells have been preliminarily confirmed [22][23][24]. Its anticancer mechanisms have been shown to be diverse, including the promotion of apoptosis, activation of endoplasmic reticulum stress, acceleration of Fe 2+ -induced oxidative damage, and promotion of autophagy in cancer cells [21,35,36].…”
Section: Discussionmentioning
confidence: 91%
“…Dihydroartemisinin (DHA) is a derivative of artemisinin and has been widely used as an antimalarial drug [18]. Meanwhile, it has also been reported to exert therapeutic effects against cancers [19][20][21][22][23][24]. DHA promotes cell apoptosis and inhibits cell proliferation by inducing autophagy in various carcinoma cells, including cervical carcinoma, cholangiocarcinoma, and hepatocellular carcinoma [19][20][21].…”
Section: Ivyspringmentioning
confidence: 99%